Parotid cancers: clinical and therapeutic study - Sarroca, Carlos (Cirugía del Uruguay, 1979)
The author has complied a series of 106 parotid tumors, in the University of Montevideo Medica! School Hospital. It is characterized by the low incidence of this condition which, however, presents high cancer rate. These growths appear in aged patients, in the form of vofuminous tumors that have had a long period of evolution and have, in most cases, extended considerably.